Differences in Growth of Children with Autism and Normal in Surabaya, Indonesia - Dewi Setyowati, - (R.K. Sharma, Institute of Medico-Legal Publications, 2019)
Background: Children with syndrome spectrum disorder wherein danger of a compromised dietary intake and biological process standing that might impact growth over each the short and long run. Children and youth with a disability were deemed to be at greater risk of obesity due to lower levels of physical activity, inappropriate behaviors associated with their disability, medication and related chronic health conditions. Aim: To evaluate the growth status of children who were diagnosed with ASD in comparison with healthy controls. Method: This research was a cross-sectional analytic study using questionnaire instruments to guardians and also direct measurements to respondents. The number of respondents for the group of children who have autism was 30 children and normal groups of children as many as 60 children. The independent variables in this study were children, autism and socio-economic, while the variables depend on body weight according to age, height according to age and head circumference according to age. This data was analyzed using the Mann Whitney U test. Results: The results of the study of 30 children with autism and 60 normal children obtained a percentage of children suffering from autism and normal children in the same good nutritional status as many as 76.67%. Height according to age for children suffering from autism in normal conditions is 66.66% and normal children are larger 83.33%, while for head circumference according to age children with autism and normal children are 100% normal. After statistical tests using SPSS 23 with α = 0.05, p = 0.987 was found for body weight according to age, p = 0.650 for height according to age and p = 1 for head circumference according to age. Conclusion: There was no difference in body weight, height, and head circumference according to age between children with autism and normal so that it could be said that children who have limitations in this case autism have normal growth like other children.